Identification of potential inhibitors of human hexokinase II for the development of anti-dengue therapeutics - Tanbin, Suriyea (Kulliyyah of Engineering, International Islamic University Malaysia, 2021)
Dengue is one of the most common arthropod-borne viral illnesses caused by the dengue virus (DENV). Approximately, 400 million dengue infections occurred every year globally, where in Malaysia a total of 82,753 dengue cases with 133 deaths were reported until October 31, 2020. The lack of effective dengue treatment leads to an increased number of cases and deaths around the globe each year. Thus, novel anti-dengue therapies are urgently needed for effective treatment. It has been reported that a glycolytic enzyme, the human hexokinase II (HKII) has a great impact in supporting viral replication in the host cell, hence the enzyme has been proposed as a drug target. The overall aim of this work is to identify novel anti-dengue drug candidates through in silico screening and HKII enzymatic inhibition studies. The potential drug candidates were screened using Ultrafast Shape Recognition with CREDO Atom Types (USRCAT) program by utilizing both HKII’s substrate and product; alpha-D-glucose (GLC) and beta-D-glucose-6-phosphate (BG6), as well as a known HKII’s inhibitor, 2-deoxyglucose (2DG), as the query molecule. In total, selected 150 compounds with the highest similarity scores relative to three reference molecules (GLC, BG6, and 2DG) were obtained from USRCAT. The similarity scores of GLC, BG6, and 2DG analogs ranged from 0.99−0.91, 0.81−0.78, and 0.80−0.75, respectively. The selected analogs were subsequently docked against each domain of the HKII structure (PDB ID: 2NZT) using the AutoDockVina program (Version 4.2.5). The six top-ranked compounds with the best docking results for each analog were observed in the N-terminus of Chain A of HKII. The binding energy of analogs of GLC, BG6, and 2DG ranged from -7.2 to -6.7 kcal/mol, -7.8 to -7.0 kcal/mol, and -6.3 to 5.0kcal/mol, respectively. Subsequently, molecular dynamic simulations were conducted using GROMACS (Version 5), where the top two analogs for each query GLC, BG6, and 2DG were selected based on strong protein-ligand stability. Meanwhile, the recombinant HKII gene has been cloned into pET28b and pET32b vectors and successfully expressed in Escherichia coli BL21 (DE3) and BL21(DE3) PlySs strains at 18°C for 20 hours, with 0.5mM IPTG induction. The expressed protein was subsequently purified with a specific activity of 80. 90U.mg-1 and 10.50% yield of 80 mg HKII protein by conducting a two-stage purification procedure. In the current study, the Vmax and Km value for HKII were determined to be 12.53uM/min, and 0.7 mM, respectively. Lastly, the inhibition analysis was conducted at different concentrations where chitin (the analog of 2DG) and 3,4-dihydroxy-5-(hydroxymethyl) (the analog of BG6) have shown a significant inhibitory effect on HKII with 36.32% and 29.58% inhibition respectively at 2mM concentration. In conclusion, among the selected compounds, chitin, which is the analog of 2DG has shown the highest inhibitory effect on human HKII, which has paved the path towards the development of future anti-dengue therapeutics.